An investigation into translating stylistic devices in “Cho tôi xin một vé đi tuổi thơ” by Nguyễn Nhật Ánh into English in “Ticket to childhood” by William Naythons - Võ, Thị Vân Vân. (The University of Da Nang, 2016)
Introduction; Literature review and theoretical background; Research methodos; ...